Lean principles adoption in environmental management system (EMS) - ISO 14001 - Perumal Puvanasvaran; Robert Kerk Swee Tian; Vasu Suresh; Muhamad (Journal of Industrial Engineering and Management (JIEM), 2012)
Purpose: The purpose of this study is to examine the characteristic of the lean principles into ISO 14001 and to propose linkage of the lean principles and ISO 14001. Design/methodology/approach: To achieve the objective of the study, literature survey and quantitative research method using questionnaires survey are used. Findings and Originality/value: The findings of this study confirm that ISO 14001 certified company adopted lean production practices. The study also proves that lean principles have positive and significant relationship with ISO 14001 EMS and the linkage can be made between lean principles and ISO 14001 to achieve Continual Improvement. Research limitations/implications: The small sizes of the sample of the participating companies are the main limitations of this study and this research mainly focuses on the manufacturing environment and services industry. Practical implications: This research show that all ISO 14001 companies do adopt at least one lean production practices and the main findings are lean principles has positive and highly significant relationship with ISO 14001 requirements. This is because the integration of lean principles into ISO 14001 will serve practical methods for ISO14001 EMS to achieve the continual improvement. Originality/value: This research is amongst the first to study the combined lean principles with ISO 1400. Based on the current situation, there is no integration within this two management system.
Keywords: 650; Lean Principles; EMS; ISO 14001; Integration